Sphenoorbital meningiomas: surgical management and outcome. (August 2014) - Forster, Marie-Thérèse; Daneshvar, Keivan; Senft, Christian; Seifert, Volker; Marquardt, Gerhard
<x content-type="archive" xml:space="preserve">Abstract</x> Objective: Surgical management of sphenoorbital meningiomas ranges among the most complex of intracranial tumors. We report on our experience of surgical technique, outcome, and tumor recurrence in sphenoorbital meningiomas. Methods: Between 2003 and 2013, surgical resections for sphenoorbital meningioma were performed in 18 patients (aged 49·6±9·8 years, only women), with two patients operated anew due to tumor recurrence. Results: Main symptom was proptosis (83·3%), followed by diminished visual acuity (38·9%), and dizziness (11·1%). In all patients the lateral orbital wall was resected, whereas the orbital roof and the zygoma were removed according to the extent of their tumorous infiltration. Unroofing of the optic canal was performed in 10 cases (55·6%) and unroofing of the optic foramen in two (11·1%). For reconstruction split calvarian bone and titanium mesh were used in six (33·3%) and seven patients (38·9%), respectively; in one patient both techniques were applied. In five patients (27·8%), no reconstruction was necessary. Complete tumor resection (Simpson grade 1 and 2) was achieved in 14 cases (77·7%). Postoperatively, proptosis improved in all patients. Median follow-up was 39·5±33·3 months (range 1–105) in 16 patients; 2 patients were lost to follow-up. No tumor recurrence was noted in five (27·8%) patients, whereas in nine (50%) patients tumor remnants proved stable over time. Two (11·1%) patients experienced progression of residual tumor, resulting in reoperation after 27 and 109 months, respectively. Discussion: Despite their delicate anatomical relations, surgery of sphenoorbital meningiomas is safe when combining modern techniques.